2021
DOI: 10.1002/lio2.662
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of surgery in prestyloid parapharyngeal tumors: Lateral approaches vs transoral robotic surgery

Abstract: Objective: Surgery is the standard treatment for most tumors in the prestyloid parapharyngeal space (PPS) but it can be a challenging procedure because of the anatomical complexity of the area. Prestyloid surgery can be performed with various lateral approaches or with a medial approach using transoral robotic surgery (TORS)-either alone or in combination with a transcervical incision. We have retrospectively compared our center's results with lateral and medial approaches.Methods: Between 2015 and 2020, 28 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Thus, many studies supported that the video endoscope of the Da Vinci robot offers a large, magnified view of confined spaces of most surgical fields in otolaryngology, which may be associated with better operative outcomes than those of conventional approaches [ 10 , 11 , 12 ]. The TORS-related shorter hospital length and fewer postoperative complication rates were additional perceptions of European OTOs that corroborate the findings of the literature [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, many studies supported that the video endoscope of the Da Vinci robot offers a large, magnified view of confined spaces of most surgical fields in otolaryngology, which may be associated with better operative outcomes than those of conventional approaches [ 10 , 11 , 12 ]. The TORS-related shorter hospital length and fewer postoperative complication rates were additional perceptions of European OTOs that corroborate the findings of the literature [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 86%
“…Further efforts are needed to develop robotic programs in European academic centers according to the potential advantages of TORS over conventional head and neck surgeries [ 13 , 14 ]. An American study reported that training was associated with a lower rate of positive margins compared to non-robotic surgery [ 25 ].…”
Section: Discussionmentioning
confidence: 99%